Bibliometric and visual analysis of doxorubicin-induced cardiotoxicity - Lin, Xiaoxiao; Wu, Guomin; Wang, Shuai; Huang, Jinyu (Frontiers in Pharmacology, 2023)
Background: Doxorubicin-induced cardiotoxicity represents a prevalent adverse effect encountered in patients undergoing treatment with doxorubicin. To date, there has been no bibliometric study to summarize the field of doxorubicin-induced cardiotoxicity. In our study, we aim to determine the current status and frontiers of doxorubicin-induced cardiotoxicity by bibliometric analysis. Methods: The documents concerning doxorubicin-induced cardiotoxicity are obtained from the Web of Science Core Collection database (WOSCC), and VOSviewer 1.6.16, CiteSpace 5.1.3 and the WOSCC's literature analysis wire were used to conduct the bibliometric analysis. Results: In total, 7021 publications were encompassed, which are produced by 37152 authors and 6659 organizations, 1323 journals, and 101 countries/regions. The most productive author, institution, country and journal were Bonnie Ky with 35 publications, University of Texas with 190 documents, the USA with 1912 publications, and PLOS ONE with 120 documents. The first high-cited article was published in the NEJM with 8134 citations authored by DJ Slamon et al in 2001. For keyword analysis, there are four clusters depicted in distinct directions. The keywords in the red cluster are oxidative stress, apoptosis, and cardiomyopathy. The keywords in the green cluster are cardiotoxicity, heart failure, and anthracycline. The keywords in the blue cluster are chemotherapy, trastuzumab, and paclitaxel. The keywords in the purple cluster are doxorubicin, adriamycin, and cancer. Most of the documents were derived from the USA, China and Italy (4080/7021, 58.1%). The number of studies from other countries should be increased. Conclusions: In conclusion, the main research hotspots and frontiers in the field of doxorubicin-induced cardiotoxicity include the role of doxorubicin in cardiotoxicity, the mechanisms underlying doxorubicin-induced cardiotoxicity, and the development of treatment strategies for doxorubicin-induced cardiotoxicity. More studies are needed to explore the mechanisms and treatment of doxorubicin-induced cardiotoxicity.